Augmented Reality Systems for Immediate-Action Commander Training During Disasters (International Conference on Computers in Education, 2016)
Disaster education focusing on how we should take immediate actions after disasters strike is essential to protect our lives. We proposed Immediate-Action Commanders (IACers) training and prototyped three IACers training systems using augmented reality (AR) and head-mounted displays (HMDs). The systems superimpose interactive virtual objects onto HMDs’ real-time vision or a trainee’s actual view.